한 중소병원의 마케팅전략수립을 위한 실증적 연구 - 변주선 (연세대학교 보건대학원, 1988)
[한글] 국민의 소득 수준 향상과 의료 기술의 발달에 따라 자유 방임적인 의료전달 체계하에서 병원 상호간의 경쟁이 심화되고 있으며 특히 규모가 작은 중소병원의 경우 상대적으로 경쟁이 불리해져 경영상의 문제가 심각히 대두되고 있다. 이 연구에서는 한 진료권 내에서 환자들의 병원 선택 요인을 기초로 연구대상 병원인 D병원의 상황 분석과 함께 진료권 내 주민과 개원의 그리고 D병원의 내원 환자를 중심으로 마케팅 조사를 통한 구체적인 마케팅 믹스를 중심으로 전략을 수립하고자 하였다. 연구 결과는 다음과 같다. 1. 진료권내 주민의 병원 선택에 가장 중요한 요인은 신뢰 요인이었는데 중환자를 믿고 맡길 수 있는 정도, 친근감, 현대적 장비, 훌륭한 의사, 이웃에 권유할 수 있는 정도, 이용 편리성 등이 주요 사항이었다. 2. 진료권 내 개원의의 환자 후송 병원의 선정요인은 의료 장비의 이용, 접근도, 전문 과목 의뢰 순으로 높았다. 그러나 D병원과 같은 중소 규모병원에 있어서는 현대적 의료장비의 이용(85.8%), 신뢰성 (77.6%), 의료 수가(61.2%)순 이었다. 3.시장 조사의 필요성을 토대로 전략 과목인 내과를 선정하여 다른 진료과와 비교한 결과 D병원의 내원 환자는 의사의 자세한 설명, 전문 분야의수, 최신 의료장비, 의사의 처방, 병원의 시설과 같은 신뢰 요인이 중요하였다. 4. 내원환자의 인적, 사회적 특성에 따라 내과에서 의사의 설명이해도가 낮은 것을 증진시켜야하고, 특히 D병원이 진료권 내에서 경쟁 우위를 확보하기 위하여는 남성, 29세 이하군, 수입 정도가 낮은 군, 교육 정도가 낮은 군을 대상으로 의사의 자세한 설명이 요구된다. 이상과 같은 분석 결과에 의하여 진료권 내 주민의 병원 선택 요인인 신뢰도를 중심으로 D병원이 진료권 내에서 경쟁 우위를 확보하기 위해서는 전략과목인 내과를 전문화시키기 위한 노력이 요구되며 특히 다른 과에 비해 의사의 설명 이해도를 환자에게 증진시키기 위한 노력이 요구된다. [영문] The purpose of this study was to develop a marketing strategy for a medium size hospital based on D hospital as a case. Three types of marketing information were collected and analyzed; information on competing hospitals and residents in the market , opinions of local clinics, and opinions of the patients visiting D hospital. The following results were obtained: 1. The most important factor influencing residents' decision to select a hospital was the credibility factor which includes a willingness to refer severe patients, closeness to the hospital, modernization of medical equipments, the reputation of doctors and accessibility. 2. The factors influencing decision to select the referral hospitals by local physicians within the market area were modernization of equipments, their accessibility to the hospital, and the degree of specialty of the hospital. (This refers to the order of importance.) The local physicians suggested that the fellowing areas of improvement for medium hospitals in general: modernization of the equipments (85.7%), credibility (77.6%), and medical charges (61.2%). 3. In order to build up credibility of the department of internal medicine of D Hospital which was selected as a strategic unit, the fellowing factors were identified; doctor's explanation, the number of specialties, modernization of medical equipments, appropriateness of doctor's prescription and hospital facilties. As an implication for further study, the more detailed explanation seemed to be required for the following groups ; male, under 29 year old, low income group, and less educated group.
보건학과/석사